A quality of life assessment and the correlation between generic and disease-specific questionnaires scores in outpatients with chronic liver disease-pilot study - Obradovic Milica; Gluvic Zoran; Petrovic Nina; Obradovic Milan; Tomasevic Ratko; Dugalic Predrag; Isenovic Esma R. (Sciendo, 2017)
Introduction. Chronic liver diseases (CLD) are an important cause of morbidity and mortality in general population. The aim of this study was to analyze potential differences between patients with CLD and healthy control group, and to estimate the severity of CLD by using simple questionnaires: general health questionnaire (GHQ-12) and chronic liver disease questionnaire (CLDQ). Methods. A cross-sectional pilot study was performed in Zemun Clinical Hospital during years 2014 and 2015. Sixty participants were divided into 4 groups (15 per group): chronic alcoholic hepatitis, other chronic hepatitis, liver cirrhosis, and healthy control group. Entire study population chose one of four offered answers of structured questionnaires GHQ-12 and CLDQ, based on which mean model of end-stage liver disease (MELD) and Child-Turcotte-Pugh (CTP) scores were calculated. Results. Mean GHQ12 and CLDQ scores were 10.5 and 5.21 ± 1.11 respectively. Regarding certain CLDQ domain scores, a significant difference between alcoholic and non-alcoholic hepatitis groups in the worry domain was observed. Mean MELD score was 7.42 ± 2.89 and did not differ between chronic hepatitis groups, while mean CTP score was 5.73 ± 0.88. A statistically significant correlation was observed between GHQ12 and CLDQ scores (ρ = -0.404, p < 0.01), but not between subjective and objective scores. Conclusions. Mean GHQ12 and CLDQ scores pointed out to general psychological no-distress condition of the studied participants, as well as scarcely expressed CLD-specific complaints. Mean MELD and CTP scores indicated stable chronic liver diseases, with low three-month mortality rates in the cases of chronic hepatitis, as well as determination to Child A group in the case of liver cirrhosis.